Formulasi Dan Uji Aktivitas Tabir Surya Gel Kitosan Menggunakan Karbopol 940 Dan Hpmc K100 Sebagai Gelling Agent - Ahmad Fahrezi, Mukhlis; Nopiyanti, Vivin; Priyanto, Widodo (Jurnal Farmasi (Journal of Pharmacy), 2021)
Ultraviolet (UV) radiation can penetrate the epidermis layer of the skin so that it can irritate and damage skin tissue. Chitosan containing chitin compounds has the potential to provide protection against ultraviolet (UV) exposure. This study aims to determine the activity of chitosan gel sunscreen seen from the SPF value, the influence of the use of variations in concentration in a combination of carbopol and HPMC as a gelling agent on the activity of chitosan gel sunscreens, concentration variations in the combination of carbopol and HPMC which are able to provide good physical properties and gel stability. The variation of concentration in the combination of carbopol and HPMC as a gelling agent was made into 3 formulas, F1 (100% carbopol: 0% HPMC), F2 (50% carbopol: 50% HPMC), F3 (0% carbopol: 100% HPMC). Chitosan gel sunscreen activity test was carried out with the SPF (Sun Protection Factor) test using UV-VIS spectrophotometry. The SPF value price is calculated using the mansyur method. SPF test results were statistically analyzed using One Way ANOVA. SPF test results from variations in concentration in a combination of carbopol and HPMC as a gelling agent, F1 (9,091348), F2 (5,419107), F3 (6,437869). SPF test results that were statistically analyzed using One Way ANOVA showed that all the data tested were significantly different from the most active formula, F1 (100% carbopol: 0% HPMC) with the SPF value price 9,091348.